Cell-type-specific synaptic modulation of mAChR on SST and PV interneurons - Chen, Huanxin; He, Ting; Li, Meiyi; Wang, Chunlian; Guo, Chen; Wang, Wei; Yu, Baocong; Huang, Jintao; Cui, Lijun; Guo, Ping; Yuan, Yonggui; Tan, Tao (Frontiers in Psychiatry, 2023)
The muscarinic acetylcholine receptor (mAChR) antagonist, scopolamine, has been shown to have a rapid antidepressant effect. And it is believed that GABAergic interneurons play a crucial role in this action. Therefore, characterizing the modulation effects of mAChR on GABAergic interneurons is crucial for understanding the mechanisms underlying scopolamine's antidepressant effects. In this study, we examined the effect of mAChR activation on the excitatory synaptic transmissions in two major subtypes of GABAergic interneurons, somatostatin (SST)- and parvalbumin (PV)-expressing interneurons, in the anterior cingulate cortex (ACC). We found that muscarine, a mAChR agonist, non-specifically facilitated the frequency of spontaneous excitatory postsynaptic currents (sEPSCs) in both SST and PV interneurons. Scopolamine completely blocked the effects of muscarine, as demonstrated by recovery of sESPCs and mEPSCs in these two types of interneurons. Additionally, individual application of scopolamine did not affect the EPSCs of these interneurons. In inhibitory transmission, we further observed that muscarine suppressed the frequency of both spontaneous and miniature inhibitory postsynaptic currents (sIPSCs and mIPSCs) in SST interneurons, but not PV interneurons. Interestingly, scopolamine directly enhanced the frequency of both sIPSCs and mIPSCs mainly in SST interneurons, but not PV interneurons. Overall, our results indicate that mAChR modulates excitatory and inhibitory synaptic transmission to SST and PV interneurons within the ACC in a cell-type-specific manner, which may contribute to its role in in the antidepressant effects of scopolamine.